(untitled) - Ferguson, Everett; (1933-...) (U.S.A., 2009)
This magisterial volume is a comprehensive survey of the doctrine and practice of baptism in the first five centuries of Christian history, arranged geographically within chronological periods. Baptism in the Early Church covers the antecedents to Christian baptism and traces the history of Christian doctrine and practice from the New Testament through the writings of the church fathers of the fourth and fifth centuries. The book deals primarily with literary sources, though it also gives attention to depictions of baptism (primarily of Jesus) in various art forms and the surviving baptismal fonts.
Keywords: Baptism -- History Early Church, 30-600